Discourse between Criminalization and Marginalization (Teks Analysis) - Manap, Solihat; Imansyah, Hidayat (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the Criminalization Discourse in the News Text "Tiran Tiran dari Tanah Wadas", as the object of research published in Tempo magazine edition of 28 February-6 March 2022. The research approach is qualitative using Norman Fairclough’s critical discourse analysis study. The subjects analyzed are criminalization and marginalization contained in the text. The research data was obtained through literature study, observation, in-depth interviews, documentation, and online data searching. The results showed that the criminalization discourse in the news text "Pelawan Tiran Dari Tanah Wadas" contained three stages according to the critical discourse analysis according to Norman Fairclough: The text includes representation, relations, and identity, where the siege of hundreds of TNI and Polri officers with criminalization and repressive actions is an effort the government to accelerate the mining plan by coercion and overriding the rights of the Wadas villagers to maintain their living space. Discourse Practice which focuses on the production and consumption of texts, Tempo as a press institution has a social control role, in this case trying to raise the voice and rights of Wadas citizens through their writings, to help criticize the policies of the Indonesian government. The conclusion of this study shows that the practice of criminalization and marginalization occurs in the field, acts arbitrarily, and overrides the right to life and the consent of the residents of Wadas Village to defend Wadas land. Along with that, the researchers found the ideology behind the news, namely the existence of a populist ideology.